2021
DOI: 10.14740/wjon1375
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Gastric Cancer to the Colon

Abstract: Gastric cancer is one of the most common and deadly cancers worldwide, especially amongst older males. Current data suggest gastric cancer is the fifth most common neoplasm and the third most deadly cancer, with an estimated 783,000 deaths in 2018. Risk factors associated with the development of gastric cancer include obesity, gastroesophageal reflux disease, Helicobacter pylori infection, and low socioeconomic status. Diagnosis of gastric cancer can be accomplished by endoscopy, which allows the clinician to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…To investigate the characteristics of colon metastasis from gastric cancer, we summarized the reported cases of gastric cancer colon metastasis. Synchronous colorectal metastases differ from metachronous; we found 24 metachronous ( 1 4 , 6 , 14 – 29 ) ( Table I ) and 13 synchronous cases ( 5 , 25 , 30 40 ), as classified and listed in Table II . Several reports have set the boundary between synchronous and metachronous metastases as diagnosed after 2 months, 6 months, and 1 year from the primary diagnosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To investigate the characteristics of colon metastasis from gastric cancer, we summarized the reported cases of gastric cancer colon metastasis. Synchronous colorectal metastases differ from metachronous; we found 24 metachronous ( 1 4 , 6 , 14 – 29 ) ( Table I ) and 13 synchronous cases ( 5 , 25 , 30 40 ), as classified and listed in Table II . Several reports have set the boundary between synchronous and metachronous metastases as diagnosed after 2 months, 6 months, and 1 year from the primary diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…Diagnostic colonoscopy was performed in almost all cases for both metachronous and synchronous colon metastases, and the findings were polypoid or linitis plastica-like. In many of the reviewed cases, the biopsy results obtained using colonoscopy were not described, and no malignant findings were reported ( 17 , 19 , 24 , 25 , 28 , 29 ) ( Tables I and II ). In our case, more than 8 years had passed since the gastric cancer surgery, and no malignant findings were obtained upon examination.…”
Section: Discussionmentioning
confidence: 99%
“…We used the following keywords and their combinations: "colonic metastasis", "colon metastasis", "poorly differentiated", "signet ring cell", and "gastric". The search revealed only ten reports, suggesting that colonic metastasis of gastric cancer is very rare or often misdiagnosed [3,[7][8][9][10][11][12][13][14][15]. One report summarized 21 cases of colorectal recurrence more than 5 years after the resection of gastric cancer, whereas another report summarized 14 cases of colonic metastases of gastric cancer [3,8].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The metastases sites varied from the cecum to the rectum, and the number of metastases varied from single to multiple. In addition, six cases were reported by five case reports [9,10,12,14,16]. These reports indicated that the majority of gastric cancers that developed colonic metastases were poorly differentiated adenocarcinoma or signet ring cell carcinoma; however, a relationship with alpha-fetoprotein-producing gastric cancer was not described.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are further theories that have been described, but have been incompletely studied. The theory of ‘dormancy’ suggests that malignant cells may spread at the time of initial malignant presentation, deposit in distal organs, remain dormant for a period of time, and after a physiologic stress they can become active again [ 11 ]. This would explain the often long latency period between initial malignancy and distal metastases.…”
Section: Discussionmentioning
confidence: 99%